COMPARAÇÃO DE CURVAS DE RETENÇÃO E CONDUTIVIDADE HIDRÁULICA DE SOLOS TROPICAIS E TEMPERADOS NÃO SATURADOS - Poltronieri, Vinicius Rocha (2020)
Knowledge of the soil water retention curve (SWRC) and the hydraulic conductivity curve (HCC) is important in understanding the behavior of unsaturated soils. The called pedotransfer functions (PTFs) are used to transform easy to measure data, such as the